AB0434 Relation of Subclinical Ultrasound Detected Synovitis and Peripheral B-Cell Counts in Rheumatoid Arthritis Patients Treated with Rituximab. (10th June 2014) - Martinez Estupiñan, L.P.; Naredo, E.; Valor, L.; Janta, I.; Montoro, M.; Del Rio, T.; Nieto-González, J.C.; Hinojosa, M.; Bello, N.; Martínez, J.; González-Fernández, C.; Lόpez-Longo, J.; et al.
Abstract : Background: The clinical response in patients with Rheumatoid Arthritis (RA) to rituximab (RTX) has been shown to be related with the presence of B-cells in the synovi. To date this has not been proved for peripheral B-cell counts. Ultrasound (US) has proven higher sensitivity for detecting synovitis than clinical assessment. The relation of subclinical US-detected synovitis and peripheral B-cell counts in RA patients treated with RTX has not been addressed. Objectives: the aim of study was to assess the association between the presence of absolute B- cell count in peripheral blood and subclinical synovitis measured by US [B-Mode (BM) and power Doppler (PD)] in RA patients treated with RTX in clinical remission according to the attending physician. Methods: In this cross sectional study we evaluated 37 RA patients treated with RTX in clinical remission according to clinical judgment. Inclusion criteria were having received at least two cycles of RTX and having had no change in therapy in the previous 3 months. All patients underwent a blind clinical, laboratory and US assessment (BM and PD of 12 joints). A global index for B-mode synovitis (BMI; range 0–36) and a global index for synovial PD signal (PDI; range 0–36), obtained by the sum of the B-mode synovitis and synovial PD signal scores for each joint region was calculated for each patient. B-cell absolute count was determined in our routine laboratory by flow cytometry. Results: Thirty (81%) patients were female with a mean (SD) age of 60 (12) years. Sixteen (43.2%) patients were rheumatoid factor (RF) positive and 29 (78.4%) had antibodies to citrullinated peptides (ACPA). The mean (SD) disease duration was 16 years (8). Fifteen patients (40.5%) satisfied the DAS28 criteria for remission, the mean (SD) DAS28 was 3.04 (1.2). All patients had evidence of BM synovitis and 16 (43.2%) patients had synovial PD signal. There was no correlation between DAS28 and BMI and PDI (r =0.13, p=0.45; r =0.27, p=0.09, respectively). Twenty six (67.5%) patients had peripheral B-cells (>1 cell/mm 3 ). There was no difference in the B-cell count according to DAS28 (DAS28 <2.6=34.53, DAS28>2.6=49.45, p=0.52) or PDI score (PDI<1=49.48, PDI>1=35.44, p=0.54). There was no correlation between B-cell count and DAS28, BMI or PDI score (r =0.020, p=0.907; r =-0.151, p=0.371; r = -0.099, p=0.558). Conclusions: in our study we did not find any relation between subclinical synovitis measured by US and peripheral B-cell count in RA patients treated with RTX. References: Buch MH, Smolen JS, Betteridge N, Breedveld FC, Burmester G, Dörner T, Ferraccioli G, Gottenberg JE, Isaacs J, Kvien TK, Mariette X, Martin-Mola E, Pavelka K, Tak PP, van der Heijde D, van Vollenhoven RF, Emery P; Rituximab Consensus Expert Committee. Updated consensus statement on the use of rituximabin patients with rheumatoid arthritis. Ann Rheum Dis. 2011 Jun;70(6):909-20. Disclosure of Interest: L. Martinez Estupiñan: None declared, E. Naredo Grant/research support: UCB and MSD, Consultant for: Abbvie, Roche Farma, Bristol- Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, L. Valor: None declared, I. Janta: None declared, M. Montoro: None declared, T. Del Rio: None declared, J. C. Nieto-González: None declared, M. Hinojosa: None declared, N. Bello: None declared, J. Martínez: None declared, C. González-Fernández: None declared, J. Lόpez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol- Myers Squibb, Pfizer, UCB, L. Carreño-Pérez: None declared DOI: 10.1136/annrheumdis-2014-eular.4136